USER PERCEPTION OF SERVICE QUALITY IN IIM LIBRARIES: A LIBQUAL+ MODEL-BASED STUDY - Pathak, Prerna; Pal, Asharam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study examines user perceptions of service quality in the libraries of six Indian Institutes of Management (IIMs)—IIM Kozhikode, IIM Indore, IIM Tiruchirappalli, IIM Kashipur, IIM Sirmaur, and IIM Jammu—by employing the LibQUAL+ framework. Data were collected from 180 respondents comprising MBA students, doctoral scholars, and faculty members. The findings reveal that while these libraries perform effectively in the domain of information control, particularly through the provision of digital resources and online access, service gaps remain in areas such as research support, user training, and collaborative study spaces. Comparative analysis highlights that first-generation IIMs (Kozhikode and Indore) continue to perform better than second-generation (Tiruchirappalli and Kashipur) and third-generation IIMs (Sirmaur and Jammu). The results emphasize the need for strategic improvements in newer IIM libraries to match the benchmarks set by older institutions. Recommendations include strengthening digital literacy workshops, expanding personalized research support, and redesigning library spaces to align with evolving academic needs.